(untitled) (Educator Insights: Journal of Teaching Theory and Practice, 2025)
This article examines the role of psychotherapy in children’s ability to manage stress and their readiness for life’s difficulties, the issues of psychological support in overcoming emotions and experiences related to problems and their development as strong individuals, as well as the possibility of improving self-confidence and social integration through this process.